The Effect of Dumble Weight Training and Spring Strength Training on Speed Jab's Punch - Lesmana, Indra; Hermanzoni, Hermanzoni; Argantos, Argantos; Yenes, Ronni (International Martial Arts and Culture Journal, 2025)
Studi Purpose The problem of this research is that the athletes are less than optimal in doing the speed of the jab. This study aims to determine the effect of dumbbell weight training and spring force training on the speed of the jab. Method This research is a type of quasi-experimental research. This research was carried out at the Andalas Plaza, Padang City. The time of the research implementation is from February 21 to March 21, 2021. The design of this research is "pre-test and post-test two group design". The overall population of athletes at Plaza Andalas Boxing Camp, Padang City. Sampling was taken using a total sampling technique, where the sample was male athletes, totaling 8 athletes. The types of data needed in this study are primary data and secondary data. Sources of data obtained through direct data collection in the field through tests and measurements of the sample. The instrument of this research is through a jab speed test. Result The statistical data analysis technique used the Liliefors normality test and t-test with a significant level of = 0.05. From the results of the research, the effect can be seen from the mean difference t-test where the increase in the speed of the jab in the dumble weight training group is 17 times higher than the group using the spring force training group 6 times. Thus, this value indicates that the given dumbbell weight training and spring force training have differences in increasing the speed of the jab at the Plaza Andalas Boxing Camp boxing athletes, Padang City.